The Lego movie [videorecording (DVD)] - Lord, Phil, 1977-; Miller, Chris, 1975- (Warner Bros. Entertainment, 2014)
Emmet, an ordinary, rules-following, perfectly average LEGO minifigure is mistakenly identified as the most extraordinary person and the key to saving the world. He is drafted into a fellowship of strangers on an epic quest to stop an evil tyrant, a journey for which Emmet is hopelessly and hilariously underprepared.